Survival after minimally invasive surgery in early cervical cancer: is the intra-uterine manipulator to blame?. Issue 12 (9th October 2020) - Nica, Andra; Kim, Soyoun Rachel; Gien, Lilian T; Covens, Allan; Bernardini, Marcus Q; Bouchard-Fortier, Geneviève; Kupets, Rachel; May, Taymaa; Vicus, Danielle; Laframboise, Stephane; Hogen, Liat; Cusimano, Maria C; et al.
Abstract : Objectives: Minimally invasive radical hysterectomy is associated with decreased survival in patients with early cervical cancer. The objective of this study was to determine whether the use of an intra-uterine manipulator at the time of laparoscopic or robotic radical hysterectomy is associated with inferior oncologic outcomes. Methods: A retrospective cohort study was carried out of all patients with cervical cancer (squamous cell carcinoma, adenocarcinoma or adenosquamous carcinoma) International Federation of Gynecology and Obstetrics 2009 stages IA1 (with positive lymphovascular space invasion) to IIA who underwent minimally invasive radical hysterectomy at two academic centers between January 2007 and December 2017. Treatment, tumor characteristics, and survival data were retrieved from hospital records. Results: A total of 224 patients were identified at the two centers; 115 had surgery with the use of an intra-uterine manipulator while 109 did not; 53 were robotic and 171 were laparoscopic. Median age was 44 years (range 38–54) and median body mass index was 25.8 kg/m 2 (range 16.6–51.5). Patients in whom an intra-uterine manipulator was not used at the time of minimally invasive radical hysterectomy were more likely to have residual disease at hysterectomy (p<0.001), positive lymphovascular space invasion (p=0.02), positive margins (p=0.008), and positive lymph node metastasis (p=0.003). Recurrence-free survival at 5 years was 80% in the no intra-uterine manipulator group and 94% in the intra-uterine manipulator group. After controlling for the presence of residual cancer at hysterectomy, tumor size and high-risk pathologic criteria (positive margins, parametria or lymph nodes), the use of an intra-uterine manipulator was no longer significantly associated with worse recurrence-free survival (HR 0.4, 95% CI 0.2 to 1.0, p=0.05). The only factor which was consistently associated with recurrence-free survival was tumor size (HR 2.1, 95% CI 1.5 to 3.0, for every 10 mm increase, p<0.001). Conclusion: After controlling for adverse pathological factors, the use of an intra-uterine manipulator in patients with early cervical cancer who underwent minimally invasive radical hysterectomy was not an independent factor associated with rate of recurrence.